(untitled) (Experimental biology, 2015)
Investigated visceral relationship vegetovascular persons with disabilities in the dynamics of work and the development of physical fatigue and their correction by adequate thermal stimulation. The objective of this research was to clarify the influence of the temperature of adequate stimulation of thermosensitive areas of the skin on the autonomic parameters at dosed physical load and identify the most important ones for the correction of functional state of body and enhance human performance.